Islamophobia in education: perceptions on the use of veil/niqab in higher education - Hanif Cahyo Adi Kistoro; Badrun Kartowagiran; Eva Latipah; Ngainun Naim; Himawan Putranta; Darmanto Minggele (Indonesian Journal of Islam and Muslim Societies, 2020)
The phenomenon of the development of the veil in Indonesia, especially among higher education has become a concern lately. This is due to the view of the public about the relationship between the use of the veil with the influence of certain ideologies. This research aims to determine the reasons and motivations for the use of the veil among female students, perceptions received in the surrounding environment, and obstacles encountered. This research uses a phenomenological approach as part of qualitative research. Participants in this research were 12 female students from private universities in Yogyakarta. The method of in-depth interviews using interview guide instruments becomes a technique in collecting data. Data analysis using semantic reduction is done by identifying important statements from the results of the interview, determining the theme of the discussion, and describing the significance of the whole experience of veiled students. The results showed that there were five main themes in the use of the veil in higher education, namely the average age of female students who used veil, motivation and reasons for using a veil, perceptions from within themselves and their environment, constraints encountered, and consistency in wearing a veil. Some of the findings obtained are certainly new references that need to be further developed. Therefore, knowledge about Islamophobia especially the perception of the phenomenon of the veil is important for educational institutions in determining policy and for the community to be a reference in dealing with the phenomenon.